Review Paper : Biofortification of maize: An Indian perspective - Gupta, H.S.; Hossain, Firoz; Muthusamy, Vignesh (The Indian Journal of Genetics and Plant Breeding, 2016)
Micronutrient malnutrition particularly prevalent in resource poor families in the developing world has emerged as a major health challenge. Billions of people worldwide suffer from impaired growth and development owing to insufficient supply of essential amino acids, vitamins and minerals leading to significant economic losses. India is home to a large number of undernourished people warranting immediate interventions. Maize is a staple crop with diverse end uses; thus micronutrient enriched maize holds immense promise for sustainable and cost-effective solutions to overcome malnutrition. We present here a review on status, constraints and opportunities in developing biofortified maize cultivars with enhanced protein quality,provitamin A,and kernel -Fe and -Zn. Quality protein maize possessing higher lysine and tryptophan is a classical example of how its successful adoption has resulted in significantly reducing malnutrition. Novel genetic variants of crtRB1 and lcyE genes have opened up new avenues for food-based solution to vitamin A deficiency. Availability of variation for kernel -Fe and -Zn and the possibility for manipulation of anti-nutritional- and promoting- factors offer distinct opportunity to deliver bioavailable minerals through diet. Development of multinutrient rich maize would help in achieving nutritional security in a more holistic way. Possible interventions to overcome the challenges of slow dissemination of biofortified crops have also been discussed.